The correlation of Malaysia total exports with Malaysia trading & bilateral partner countries - Dailami Aiman, Bolkim (2019)
Malaysia as part of an Asean region has been growing its economy via international trade. It is viewed that in the GDP theory, net exports increase the GDP growth including Malaysia in this context. The objective of this research paper is to examine the correlation between Malaysia total export and the 1 1 major trading countries. In addition, it will oversee the importance of Malaysia total exports variables such as export industry and bilateral free trade agreement. This study examines the correlation between Malaysia total exports to the world and the 1 1 major trading partner countries. Panel data of Malaysia total exports to 1 1 countries from 2011-2017 will be analysed based on industries such as electrical & electronics, petrochemical, palm oil and rubber to conduct the correlation analysis. Singapore recorded the highest correlation with Malaysia's total export. On the other hand, among the Malaysia bilateral trade partner countries, the palm oil sector has the highest correlation with Malaysia total exports. The findings of this study concluded that in this modem era Bilateral FTA benefits outweigh Multilateral FT A for Malaysia export performance. To a certain extent due to Malaysia's relative competitive advantage of its resources it can export to developed countries like Germany and USA without so much aid from multilateral FTA.